Problems of ensuring the food security - SAGINOVA, Saniya; DOSKALIYEVA, Bayan; SAPAROVA, Gulnar; TLEUZHANOVA, Manatzhan; KASENOVA, Asiya; TEMIRBULATOV, Alken (Journal of Advanced Research in Law and Economics, 2017)
The processes of development of human society are accompanied by population growth, which causes the most acute problem of providing people with food. The scientific article outlines the processes of formation and development of modern technologies for the production of competitive agricultural products based on the use of nanotechnology. The possibilities of nanotechnology in improving the viability of animals and poultry, increasing their productivity and economic efficiency of production are presented. Processes have been identified to improve the quality of agricultural products in crop production and to obtain environmentally friendly food for humans. Based on the study of the experience of foreign countries, an analysis of the budgetary allocations of developed countries to research in the field of nanotechnology is presented. It is revealed that the priorities of state programs are aimed at the development of technologies in the field of science and technology.